2023
DOI: 10.1097/tp.0000000000004572
|View full text |Cite
|
Sign up to set email alerts
|

An Immune Atlas of T Cells in Transplant Rejection: Pathways and Therapeutic Opportunities

Abstract: Short-term outcomes in allotransplantation are excellent due to technical and pharmacological advances; however, improvement in long-term outcomes has been limited. Recurrent episodes of acute cellular rejection, a primarily T cell–mediated response to transplanted tissue, have been implicated in the development of chronic allograft dysfunction and loss. Although it is well established that acute cellular rejection is primarily a CD4+ and CD8+ T cell mediated response, significant heterogeneity exists within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 180 publications
(261 reference statements)
0
2
0
Order By: Relevance
“…Moreover, the significant role of MIF in various biological processes and immune responses, particularly its impact on different T-cell types, underscores its potential as a biomarker or therapeutic target in islet transplantation. Compared to findings from the previous study ( 11 ), our study further elaborates on the role of γδ T cells in graft environments, providing a deeper understanding of their dual role in immunoregulation and inflammation.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Moreover, the significant role of MIF in various biological processes and immune responses, particularly its impact on different T-cell types, underscores its potential as a biomarker or therapeutic target in islet transplantation. Compared to findings from the previous study ( 11 ), our study further elaborates on the role of γδ T cells in graft environments, providing a deeper understanding of their dual role in immunoregulation and inflammation.…”
Section: Discussionmentioning
confidence: 63%
“…The heterogeneity of T-cell subpopulations and their distinct roles in transplantation immunobiology has been studied. For instance, regulatory T cells have been shown to promote graft tolerance ( 12 ), while effector T cells contribute to graft rejection ( 11 ). The phenotypic characterization of T-cell subpopulations in the context of islet transplantation has revealed potential targets for immunomodulatory therapies, indicating the potential of these cell types for improving transplantation outcomes ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recognition and rejection of allografts are the result of complex interactions between various cells. Modern transplantation immunology studies have found that GzmB plays an important role in CTL killing of donor cells (Short et al, 2023). As early as 1991, Clément et al reported that GzmB could be used as a predictive marker of acute GVHD or cardiac rejection after bone marrow or heart transplantation (Clément et al, 1991).…”
Section: Acute Cellular Rejection (Acr)mentioning
confidence: 99%
“…Historically, the research addressing allograft rejection mainly focused on the adaptive immune system, increasing the knowledge regarding different cell subsets involved in this process [15,16]. This goes back to early publications showing that T-cells played a crucial role in allograft rejection [17,18].…”
Section: Introductionmentioning
confidence: 99%